2015
DOI: 10.1177/0960327115569810
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen-induced Ca2+ movement and death in MDCK canine renal tubular cells

Abstract: Naproxen is an anti-inflammatory drug that affects cellular calcium ion (Ca2+) homeostasis and viability in different cells. This study explored the effect of naproxen on [Ca2+]i and viability in Madin-Darby canine kidney cells (MDCK) canine renal tubular cells. At concentrations between 50 μM and 300 μM, naproxen induced [Ca2+]i rises in a concentration-dependent manner. This Ca2+ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Other important mechanisms of parthenolide action include DNA synthesis inhibition (58), mitochondrial disorder induction, G 2 /M cell cycle arrest (44,53) and sustained activation of c-Jun N-terminal kinase (JNK) (42). In addition, alternation in Ca 2+ homeostasis is also involved in the bioactivity of parthenolide (47) to induce apoptosis through multiple pathways (12,13,22,37,50). Likewise, it has also been reported that parthenolide induced downregulation of a variety of antiapoptotic molecules, such as Bcl-xL, Mcl-1 and survivin in leukemia cells (31).…”
Section: Introductionmentioning
confidence: 99%
“…Other important mechanisms of parthenolide action include DNA synthesis inhibition (58), mitochondrial disorder induction, G 2 /M cell cycle arrest (44,53) and sustained activation of c-Jun N-terminal kinase (JNK) (42). In addition, alternation in Ca 2+ homeostasis is also involved in the bioactivity of parthenolide (47) to induce apoptosis through multiple pathways (12,13,22,37,50). Likewise, it has also been reported that parthenolide induced downregulation of a variety of antiapoptotic molecules, such as Bcl-xL, Mcl-1 and survivin in leukemia cells (31).…”
Section: Introductionmentioning
confidence: 99%
“…The affinity of hOCT2 for ASP + was determined by saturation experiments of specific ASP + uptake determined in the presence of increasing ASP + concentrations (0–50 µM). In further experiments, regulation of hOCT2-mediated transport was evaluated by the co-incubation of ASP + with 1 nM AII, or 1 µM DOG (a PKC activator, this concentration is known to be able to regulate OCT-activity [ 65 ]), or 40 µM rottlerin (a PKC inhibitor), or 5 µM BAPTA-AM (a Ca 2+ chelator, this concentration efficiently chelates intracellular Ca 2+ and does not compromise cell viability in MDCK cells [ 66 ]), alone or in combination. Solvents (DMSO or ethanol) at the concentration used in the regulation experiments did not change the ASP + uptake (not shown).…”
Section: Methodsmentioning
confidence: 99%
“…NSAIDs eliminate pain, but do not eliminate signs and symptoms of active disease, nor do they repair cartilage. Furthermore, the use of NSAIDs can be linked to side effects, such as hepatic and renal dysfunction [47][48][49] reduced appetite, vomiting, and gastrointestinal upset and bleeding [50][51][52][53][54]. Additionally, NSAIDs have been reported to inhibit bone healing [55].…”
Section: Introductionmentioning
confidence: 99%